Depression symptoms as a mediator between social support, non-suicidal self-injury, and suicidal ideation among Arab adolescents in Israel. (August 2021) - Madjar, Nir; Daka, Doaa; Zalsman, Gil; Shoval, Gal
The purpose of the current study was to explore whether depression symptoms mediate the relationships between perceptions of social support from three sources; namely parents, teachers, and peers, and non-suicidal self-injury (NSSI) and suicidal ideation. We also tested the interactions between the different sources of support. Focusing on the Arab-Israeli population is unique as it is an ethnic minority characterized with strong familial support, and less access to mental health services compared to the ethnic majority. Adolescents (N = 276; 65.6% girls; mean age 15.1 years) from the Arab minority in northern Israel were sampled (74% response rate). Participants were evaluated using validated scales assessing perceived social support, NSSI and suicidal ideation. Path analysis with Bayesian estimation supported the hypothesized model. Depression symptoms fully mediated the relationships between school-related social support (i.e., teachers and peers) and NSSI, and partially between parents' support and suicidal ideation. Interactions between the social support sources were not significant, and cluster analysis indicated that each source is independently essential to understand NSSI and suicide ideation. This model emphasizes the importance of school-related factors in adolescents' particular aspects of mental health, and suggests that one source of social support may not compensate for a lack of another.